Pulled elbow: A paediatrician’s experience - Regmi, Shanti (Journal of Chitwan Medical College, 2017)
Pulled elbow is a common condition but may not be recognized by most of the paediatric physician. The purpose of this study is to evaluate the common age, mechanism, site of pain, reduction maneuver and its efficacy among paediatric population. Among 40 patients, 31 patients meeting the inclusion criteria were included in this study. Simple analytical method was used to analyze the data due to small number of patients. Supination-flexion maneuver was used for reduction. Among 31, 15 (48.38%) were male and 16(51.61%) were female. The mean age was 3.12 years, mean arrival time was 13.03 hours. 32.25% of patients had history of pulling the child up and 41.93% of patient complained of pain around forearm. All patient underwent supination- flexion maneuver and was successful in first attempt, except one, that required second attempt. There were no recurrences. There should be a high index of suspicion among paediatricians, so that they can correctly diagnose and treat this condition satisfactorily.